Review of Robert Fink. 2005. Repeating Ourselves: American Minimal Music as Cultural Practice. Berkeley and Los Angeles: University of California Press - Haskins, Rob (Current Musicology, 2006)
The music of the American minimalist composers-above all, Steve Reich and Philip Glass-continues to excite an increasingly diverse, international public. DJs have hammered out artful and groovy remixes; online mavens have banded together in chat groups; and the advertising industry has licensed Glass’s music and commissioned Reich knock-offs as parts of campaigns for cars, cereal, soft drinks, and many other products. The composers have found success in more conventional venues as well. Last fall, Reich won the Edward MacDowell Medal, while Glass saw the premieres of his eighth symphony and his twenty-first opera. This unusual assortment of venues and events connected with minimal music makes it-perhaps more than any other twentieth- or twenty-first- century Western classical repertoire-admirably suited to a sustained examination of its wider cultural contexts. For the most part, however, few have ever attempted such a study. Most scholarly works on minimalism resolutely privilege its formalism and have used sophisticated music-analytical tools to explicate the music’s structure (among many fine examples, see Cohn 1993); only recently have scholars undertaken broader, culturally grounded inquiries (Grimshaw 2002). Thus, Robert Fink’s Repeating Ourselves, a major work of such cultural criticism, is long overdue. Fink, an associate professor of music at UCLA, has a lively mind that has led his teaching and scholarship in a variety of directions, from the dizzying array of genres (and subgenres) of electronic dance music to Freudian readings of Brahms and Schoenberg. In all his work, he profitably reads music against the grain to disclose unexpected cultural connections and resonances; his best work discusses popular and classical musics in such a way that he honors both without reinscribing traditional (and sometimes problematic) methods of determining their value. Fink situates American (and some European) minimal music in anumber of concurrent cultural activities. In chapter I, “Do It (’til You’re Satisfied): Repetitive Musics and Recombinant Desires;’ he counterpoises Reich’s Music for Eighteen Musicians with Donna Summer’s “Love to Love You, Baby” (both from 1976) to explore the multivalent and erotically charged teleology of minimalism and disco. Chapter 2, “‘A Colorful Installment in the Twentieth-Century Drama of Consumer Subjectivity’: Minimalism and the Phenomenology of Consumer Desire;’ examines the culture of repetitive advertising in the 1960s, theorizes it (with the help of Jean Baudrillard’s ideas of postmodernity), and briefly considers how several compositions by Reich and Glass might be heard to echo it. Fink continues this inquiry in chapter 3, “The Media Sublime: Minimalism, Advertising, and Television;’ with more sustained analyses of Reich’s Eight Lines (1979), Terry Riley’s In C (1964), Louis Andriessen’s Hoketus (1977), and “The Grid,” from Glass’s score for Godfrey Reggio’s film Koyaanisqatsi (1982). Chapter 4, ”’A Pox on Manfredini’; The Long-Playing Record, the Baroque Revival, and the Birth of Ambient Music,” considers the repetitive, mood-regulating therapy offered by automatic record changers loaded up with mediocre performances of Vivaldi, Telemann, and other composers of Baroque Tafelmusik. Finally, Fink turns to the intersections of minimalism and Suzuki violin instruction in America in chapter 5, ”’I Did This Exercise 100,000 Times’: Zen, Minimalism, and the Suzuki Method;’ and ultimately concludes that repetitive musical and social activities facilitated the minimalist process-works of the mid- and later 1960s.